Effect of Leptin on Chronic Inflammatory Disorders: Insights to Therapeutic Target to Prevent Further Cardiovascular Complication - Dessie G (Dove Medical Press, 2021)
Gashaw Dessie,1 Birhanu Ayelign,2 Yonas Akalu,3 Tewodros Shibabaw,1 Meseret Derbew Molla1 1Department of Biochemistry, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Immunology and Molecular Biology, School of Biomedical and Laboratory Science, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Physiology, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Gashaw Dessie Tel +251 975152796Email dessiegashaw@yahoo.comAbstract: In response to obesity-associated chronic inflammatory disorders, adipose tissue releases a biologically active peptide known as leptin. Leptin activates the secretion of chemical mediators, which contribute to the pathogenesis of chronic inflammatory disorders, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and psoriasis. Conversely, adiposity and obesity are the major aggravating risk factors in the pathogenesis of metabolic syndrome (MetS), including type II diabetes mellitus and obesity-associated hypertension. Elevated level of leptin in obesity-associated hypertension causes an increase in the production of aldosterone, which also results in elevation of arterial blood pressure. Hyperleptinemia is associated with the progress of the atherosclerosis through secretion of pro-inflammatory cytokines, like interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), IL-17, and other cytokines to promote inflammation. The release of those cytokines leads to chronic inflammatory disorders and obesity-associated MetS. Thus, the aberrant leptin level in both MetS and chronic inflammatory disorders also leads to the complication of cardiovascular diseases (CVD). Therapeutic target of leptin regarding its pro-inflammatory effect and dysregulated sympathetic nervous system activity may prevent further cardiovascular complication. This review mainly assesses the mechanism of leptin on the pathogenesis and further cardiovascular risk complication of chronic inflammatory disorders.Keywords: leptin, chronic inflammatory disorders, cardiovascular